Pengaruh Dukungan Keluarga Terhadap Minat Siswa Untuk Mengikuti Kegiatan Ekstrakurikuler Di SDIT Al-Izzah Serang : Hubungan Dukungan Keluarga dengan Partisipasi Siswa dalam Kegiatan Ekstrakurikuler: Studi Kasus di SDIT Al-Izzah Serang - Fatimatul Zuhroh; Sabri; Juhji (Institut Agama Islam Negeri Palangka Raya, 2025)
One of the things that can influence children's interest in participating in extracurricular activities is family support. By using three indicators, namely (1) Providing Opportunities, (2) Providing Information, and (3) Providing Facilities, as well as Arifin's indicator theory, this study aims to determine the extent to which family support influences students' interest in participating in extracurricular activities at school. This study was attended by 51 fourth grade students of SDIT Al Izzah Kota Serang. Data collection was carried out by distributing questionnaires directly with a Likert scale. The data analysis used was multiple linear regression. The results of the analysis showed 0.265 or 26.5%, while other factors not studied influenced students' interest by 73.5%. Thus, with a total influence of 26.5%, it can be said that Family Support (X) has a positive effect on Student Interest (Y). This study indicate that family support affects students' interest in extracurricular activities.